Micropropaga??o e conserva??o de Comanthera mucugensis Giul. subsp. mucugensis - Gurgel, Zafira Evelma da Rocha (2017)
Comanthera mucugensis Giul. subsp. mucugensis, an endemic species of the municipality of Mucug?-BA is threatened with extinction. To reduce extractivism in natural populations, it is necessary to develop efficient multiplication protocols; In this sense somatic embryogenesis and organogenesis may be viable and preservation cryopreservation may be a strategy for its long-term. The objectives of this study were: (1) to analyze the embryogenic competence and the indirect organogenesis of C. mucugensis; (2) to evaluate the cryopreservation of seeds and different methods of cryopreservation of C. mucugensis plants and (3) to identify the best way to store seeds in the long term. Experiments were performed to induce somatic embryogenesis with different concentrations of 2,4-D X BAP and Picloran X BAP and for indirect organogenesis BAP and ANA were used. Seeds were cryopreserved for 0 (control), 1, 7, 30, 360 and 540 days and other seeds were stored at different temperatures to verify the best form of storage. Plants were cryopreserved with the technique of vitrification and encapsulation-desiccation. Plants from cryopreserved seeds were acclimatized in sand and vegetal soil (1: 1) for 60 days. The work showed that the plant regulators Picloran and 2,4-D are promising in the induction of callus with embryogenic potential and that the plant regulator ANA at 4.9 ?M is efficient in indirect organogenesis. The seeds of C. mucugensis can be cryopreserved without compromising their physiological quality, but the techniques for cryopreservation of plants have not been efficient.